2018
DOI: 10.1210/jc.2017-02654
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Lifestyle Intervention for Overweight Women With Previous Gestational Diabetes: A Randomized Controlled Trial

Abstract: PAIGE resulted in significantly greater weight loss at 6 months compared with usual care. Such weight loss could prove beneficial in terms of better long-term health and subsequent prevention of type 2 diabetes in overweight women with previous GDM. Future interventions must consider recruitment strategies, timing of the intervention, and inclusion of partners and/or other family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…In this regard, a few RCTs of intensive interventions (lifestyle and insulin if needed) during pregnancy among women with GDM had been conducted to examine the effects of such interventions on postpartum diabetes risk, but none of them observed that interventions of GDM during pregnancy were effective in reducing the risk of diabetes after delivery 6–8 . Many RCTs had also been conducted to test the efficacy and effectiveness of postpartum lifestyle intervention for the prevention of diabetes among women with prior GDM, but most of them did not show that lifestyle modification was effective in reducing the long‐term risk of diabetes, presumably due to small sample size, relative short duration of follow‐up and hence inadequate statistical power 9–13 . Meta‐analyses may be a way to overcome the limitation of statistical power in individual studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a few RCTs of intensive interventions (lifestyle and insulin if needed) during pregnancy among women with GDM had been conducted to examine the effects of such interventions on postpartum diabetes risk, but none of them observed that interventions of GDM during pregnancy were effective in reducing the risk of diabetes after delivery 6–8 . Many RCTs had also been conducted to test the efficacy and effectiveness of postpartum lifestyle intervention for the prevention of diabetes among women with prior GDM, but most of them did not show that lifestyle modification was effective in reducing the long‐term risk of diabetes, presumably due to small sample size, relative short duration of follow‐up and hence inadequate statistical power 9–13 . Meta‐analyses may be a way to overcome the limitation of statistical power in individual studies.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Studies have also shown that postpartum behavioural weight loss interventions after delivery can help women reduce postpartum weight retention (PPWR) and risk for future obesity. [14][15][16][17] Because adults face multiple demands on their time, remote delivery (i.e. phone) of behavioural counselling and integration of such counselling within the prenatal care setting where women receive usual care has the potential to enhance patient engagement and satisfaction and to promote dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐three studies had a low risk of bias in the randomization process, most studies (>90%) had a high risk of bias in deviations from intended interventions and more than half of the studies (29/36 studies) had a low risk of bias from missing outcome data, of which 10 studies reported intention‐to‐treat analyses . Three studies were at high risk of bias from missing outcome data with a higher drop‐out rate in the intervention group and less than one‐third of the studies (11/36) had a low risk of bias from the measurement of outcome . All of the studies had a low risk of bias from selective reporting apart for two studies that analyzed the same outcomes through different methods .…”
Section: Resultsmentioning
confidence: 98%
“…The postpartum phase for recruitment ranged from 3 weeks to 12 months. 24,[28][29][30][31] Twelve studies recruited participants with overweight or obesity at baseline (i.e., in the postpartum period), 28,[31][32][33][34][35][36][37][38][39][40][41] five studies recruited women with overweight or obesity according to prepregnancy BMI, 40,[42][43][44][45] one study recruited women with excessive gestational weight gain of more than 6Á8 kg, 46 three recruited only those with postnatal depression, 24,47,48 four recruited only women with a history of gestational diabetes, 27,39,41,49 and one recruited only those with type 2 diabetes. 50 The remaining studies recruited from the general postpartum population.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation